Regulating Strip-Based Entertainment: Sexual Entertainment Venue Policy and the Ex/Inclusion of Dancers' Perspectives and Needs. Issue 1 (28th August 2014) - Sanders, Teela; Hardy, Kate; Campbell, Rosie
Abstract : This article showcases a research, dissemination and impact study on the striptease industry that explores why key stakeholders (dancers) are excluded, and ways that inclusion in policy development is achievable. This form of erotic work has undergone increased attention from policy and regulatory officials in recent years with the introduction of a new licensing process as venues are categorised as Sexual Entertainment Venues. The article will demonstrate how community and campaign group voices were heard over that of the dancers themselves, who were not consulted in the process of the legislative change. However, the article shows how small but significant interventions into policy development by direct work with stakeholders (here Licensing Committees and officers) can make steps towards an inclusion of dancer welfare and safety issues. Finally, we propose a set of principles that can ensure dancer and sex worker voices are included in policy consultation and decision making to ensure evidence-based policy making.